Job role localisation in the oil and gas industry: A case study of Ghana. Issue 2 (April 2020) - Pegram, Jack; Falcone, Gioia; Kolios, Athanasios
Highlights: Viability of localising particular job roles is analysed. A systematic decision support approach is developed. Costs of localising expat jobs is calculated for 5 typical roles. Training and development of local people can reduce costs for O&G companies. Abstract: International oil and gas companies and their contractors are increasingly required to localise job roles in order to comply with host government's local content legislations. This practice does not come without risks, costs and challenges for asset operators investing in these countries. As such, a progressive training and development process should be followed to enable oil and gas companies to replace expatriates with nationals with the relevant education, competencies and experience. This paper aims to analyse the viability of localising particular job roles, employing a systematic decision support approach for specific job roles and further investigating the result of early investment in the training and development of local people to enable oil and gas companies to reduce staffing costs by localising expatriate job roles. The proposed approach examines the case study of Ghana through engagement with appropriate stakeholders which endorse the validity of the results.